SOCIAL TOURISM AS THE GCET IMPLEMENTATION - Zuraida, Lukia; Rastitiati, Ni Kade Juli; Suasapha, Anom Hery (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
This study aims to analyze the implementation of the Global Code of Ethics of Tourism in Indonesia in the form of social tourism organized by Bali Tourism Polytechnic as the case study. Therefore, a literature review to explore the concept of social tourism, its impacts, and its relation with sustainable tourism has been carried out. Then, using those concepts as the theoretical lens, the implementation of social tourism in Indonesia is analyzed. The result reveals that the social tourism organized by the Bali Tourism Polytechnic for its lecturer and staff is tourist-related social tourism. Given its benefits for the host community visited, the social tourism of Bali Tourism Polytechnic is also host-related social tourism as well as sustainable tourism. It also shows the presents of the government of the Republic of Indonesia in providing equal opportunity for the citizen to enjoy tourism, thus confirming that the mandate of the Global Code of Ethics of Tourism and the Tourism Low of Indonesia has been met. Academic implications from this study are Contribution to Social Tourism Literature, Policy and Governance. Practical implications that this study can be a Model for Social Tourism Implementation